Soybean proteins GmTic110 and GmPsbP are crucial for chloroplast development and function. (November 2016) - Sandhu, Devinder; Atkinson, Taylor; Noll, Andrea; Johnson, Callie; Espinosa, Katherine; Boelter, Jessica; Abel, Stephanie; Dhatt, Balpreet K.; Barta, Terese; Singsaas, Eric; Sepsenwol, Sol; Goggi, A. Susana; et al.
Highlights: We identified and characterized a viable-yellow and a lethal-yellow soybean mutant. A frame shift mutation in GmTic110 resulted in the viable-yellow phenotype. A frame shift mutation in GmPsbP caused the lethal-yellow phenotype. GmTic110 and GmPsbP are vital for chloroplast biosynthesis and oxygen evolution. Mutant proteins caused photooxidative stress resulting in yellow phenotypes. Abstract: We have identified a viable-yellow and a lethal-yellow chlorophyll-deficient mutant in soybean. Segregation patterns suggested single-gene recessive inheritance for each mutant. The viable- and lethal-yellow plants showed significant reduction of chlorophyll a and b . Photochemical energy conversion efficiency and photochemical reflectance index were reduced in the viable-yellow plants relative to the wildtype, whereas the lethal-yellow plants showed no electron transport activity. The viable-yellow plants displayed reduced thylakoid stacking, while the lethal-yellow plants exhibited failure of proplastid differentiation into normal chloroplasts with grana. Genetic analysis revealed recessive epistatic interaction between the viable- and the lethal-yellow genes. The viable-yellow gene was mapped to a 58 kb region on chromosome 2 that contained seven predicted genes. A frame shift mutation, due to a single base deletion in Glyma.02g233700, resulted in an early stop codon . Glyma.02g233700 encodes a translocon in the inner membrane of chloroplast (GmTic110) that plays a critical role in plastid biogenesis. The lethal-yellow gene was mapped to an 83 kb region on chromosome 3 that contained 13 predicted genes. Based on the annotated functions, we sequenced three potential candidate genes. A single base insertion in the second exon of Glyma.03G230300 resulted in a truncated protein. Glyma.03G230300 encodes for GmPsbP, an extrinsic protein of Photosystem II that is critical for oxygen evolution during photosynthesis. GmTic110 and GmPsbP displayed highly reduced expression in the viable- and lethal-yellow mutants, respectively. The yellow phenotypes in the viable- and lethal-yellow mutants were due to the loss of function of GmTic110 or GmPsbP resulting in photooxidative stress.